Reducing Crime and Violence: Experimental Evidence from Cognitive Behavioral Therapy in Liberia - Blattman, Christopher; Jamison, Julian C.; Sheridan, Margaret (American Economic Review, 2017)
We show that a number of noncognitive skills and preferences, including patience and identity, are malleable in adults, and that investments in them reduce crime and violence. We recruited criminally engaged men and randomized one-half to eight weeks of cognitive behavioral therapy designed to foster self-regulation, patience, and a noncriminal identity and lifestyle. We also randomized $200 grants. Cash alone and therapy alone initially reduced crime and violence, but effects dissipated over time. When cash followed therapy, crime and violence decreased dramatically for at least a year. We hypothesize that cash reinforced therapy's impacts by prolonging learning-by-doing, lifestyle changes, and self-investment.